Expression of pluripotency master regulators during two key developmental transitions: EGA and early lineage specification in the bovine embryo. - Daulat Raheem Khan (Public Library of Science (PLoS), 2012)
Pluripotency genes are implicated in mouse embryonic genome activation (EGA) and pluripotent lineage specification. Moreover, their expression levels have been correlated with embryonic term development. In bovine, however, little information is available about dynamics of pluripotency genes during these processes. In this study, we charted quantitative and/or qualitative spatio-temporal expression patterns of transcripts and proteins of pluripotency genes (OCT4, SOX2 and NANOG) and mRNA levels of some of their downstream targets in bovine oocytes and early embryos. Furthermore, to correlate expression patterns of these genes with term developmental potential, we used cloned embryos, having similar in vitro but different full term development rates. Our findings affirm: firstly, the core triad of pluripotency genes is probably not implicated in bovine EGA since their proteins were not detected during pre-EGA phase, despite the transcripts for OCT4 and SOX2 were present. Secondly, an earlier ICM specification of transcripts and proteins of SOX2 and NANOG makes them pertinent candidates of bovine pluripotent lineage specification than OCT4. Thirdly, embryos with low term development potential have higher transcription rates; nevertheless, precarious balance between pluripotency genes is maintained. This balance presages normal in vitro development but, probably higher transcription rate disturbs it at later stage that abrogates term development.